The Impact of Capital Intensity, Size of Firm and Firm’s Performance on Debt Financing in Plantation Industry of Sri Lanka - Yogendrarajah, R.; Gamlath, G.R.M. (International Conference on Management and Economics, Faculty of Management and Finance, University of Ruhuna., 2013)
This paper investigates on debt financing, considering as an important source of finance for firms’ all long term and short term operating requirements of the firms. The percentage of debt financing in capital structure is affected by the profitability and growth of companies. This objective of the study attempts to find out the impact of capital intensity, size of the firm and firm’s performance on debt financing in plantation sector in Sri Lanka. This study measures the capital structure determinants in terms of capital intensity(CI), size of firm ( Log of Total Assets - LTA), financial performance (NPM, ROA and ROCE) where as capital structure is measured by debt to equity financing ratio (DER). The relationship is examined using the regression analyses by using a sample of 09 plantation companies (as a pioneering and well performing business industry in Sri Lankan economy) covering the period of 2007-2011. The results show that, there is significant impact of the variables on firm’s debt financing. The study indicates that the proportion of debt financing in capital structure is affected by the profitability, size and capital intensity of the firms in plantation sector of Sri Lanka. The financial managers should therefore make trustful decisions must to be taken in terms of capital structure changes, keeping in view the impact of capital intensity, size of firm, firm’s performance with concentrating macro economic factors as well as it would help in suggesting future financial reforms for the sector as required.
Keywords: Debt Financing; Capital Intensity; Size of Firm; Firm’s Performance